2011
DOI: 10.1002/adma.201004637
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of BMP‐2 from a Soft Biopolymeric Film Unveils its Activity on Cell Adhesion and Migration

Abstract: International audienceThe dramatic effect of morphogenetic protein 2 (BMP-2), presented to cells in a "matrix bound" manner is described. BMP-2 is either delivered in solution or bound to a thin film made of poly(lysine) and hyaluronan. In this later case only, a striking effect of BMP-2 on cell adhesion and migration is observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(181 citation statements)
references
References 49 publications
13
165
0
1
Order By: Relevance
“…165 Matrix binding has been shown to enhance growth factor function over that of the soluble form. 42 In vivo, other cells, such as fibroblasts, may also respond to a chemoattractant by migrating and/or by producing growth factors and chemokines. 58 Testing in animal models showed that lower doses of growth factor resulted in a greater chemotactic response 53 and that chemotaxis in vitro may not correspond to chemotaxis in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…165 Matrix binding has been shown to enhance growth factor function over that of the soluble form. 42 In vivo, other cells, such as fibroblasts, may also respond to a chemoattractant by migrating and/or by producing growth factors and chemokines. 58 Testing in animal models showed that lower doses of growth factor resulted in a greater chemotactic response 53 and that chemotaxis in vitro may not correspond to chemotaxis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials and strategies for chemoattractant delivery are described elsewhere. 31,42 In recent years, a substantial body of work has been published in which various chemoattractants have been tested for MSC recruitment in vitro and in several in vivo models. The objective of this review is to synthesize and evaluate evidence of recruitment efficacy by reported MSC chemoattractants.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactivity of growth factors presented in an immobilized form has also been shown in other studies, indicating that the release of the proteins and their subsequent internalization are not essential for cell stimulation 24,25 . In fact, the covalent immobilization of growth factors allows the sustained stimulation of the target cells while maintaining an effective dosage because of enhanced occupancy rate of different types of receptors at the cell membrane 22,23,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…soluble, on a fluid substrate, or immobilized) and if the nature of the receptors plays a role. This issue has been illustrated by the different cellular responses elicited by identical growth factors depending on whether they are soluble or attached to the surrounding matrix (Crouzier et al, 2011).…”
Section: Ecm Sensingmentioning
confidence: 99%